AKTIVITAS PENGHAMBAT ENZIM PROTEASE 6LU7 VIRUS SARS-COV-2OLEH SENYAWA DARI SPONGE(Filum Porifera) SECARA IN SILICO - Kesaktian Manurung; Siti Maimunah; Fitri Yulia Sari (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
The metabolite content in sponge has a unique chemical structure and very interesting pharmacological activity, such as anticancer, antimicrobial, anti-inflammatory, antifouling, antifouling, and inhibiting enzyme activity. The purpose of this study is to find out the value of RMSD in protein validation 6LU7 in silico, to know the ability of Sponge compounds in inhibiting protease enzyme 6LU7 from SARS-CoV-2 Virus in silico, and to know the comparison of the results of docking score of Sponge compounds in the inhibition of protease enzyme 6LU7SARS-CoV-2 virus to visualize docking results to know the amino acids that bond with each other. This research is a descriptive study that is to test the activity of Sponge compounds against inhibition of protease enzyme 6LU7 SARS-CoV-2. The phases in this study include downloading and installation applications needed. And validation of in silico tethering method to protease enzyme 6LU7 SARS-CoV-2 virus, as well as the docking of Sponge compound molecules against protease enzyme 6LU7 SARS-CoV-2 virus in silicon. The results of the study obtained that the process of tethering protease enzyme 6LU7 sars-cov-2 virus is declared valid so that it can be used for molecular tethering of Sponge test compounds in silico. Sponge test compounds can inhibit the protease enzyme 6LU7 Sars-CoV-2 virus. The docking score of Sponge test compounds on protease enzyme 6LU7 SARS-CoV-2 virus is lower than the comparison. As the result of docking visualization, several amino acid residues interact with each other including hydrogen bonds.